Vibration-stimulated gas pressure cycling (VS-GPC) process with a frequency modulation for optimizing heavy oil recovery - Shixuan Lu; Zhengyuan Zhang; Liming Dai; Na Jia (Journal of Petroleum Exploration and Production Technology)
Abstract This research aims to develop a vibration-stimulated gas pressure cycling (VS-GPC) process with frequency modulation to enhance heavy oil recovery. The study examines four types of VS-GPC processes and compares their performance against the conventional gas pressure cycling (GPC) process. The effects of heavy oil viscosity, vibration frequency variation, and the presence of a soaking period on heavy oil recovery and gas production are analyzed. The developed VS-GPC process significantly increases heavy oil production during different production cycles when proper frequency vibrations are applied, demonstrating a major breakthrough in optimizing extraction techniques. Experiments show that low-frequency vibrations facilitate oil recovery in early cycles by mobilizing oil in far-end regions, while high-frequency vibrations enhance recovery in later cycles near the injector region. Additionally, the necessity of incorporating soaking periods is confirmed, as omitting them markedly reduces the recovery factor (RF). This research strengthens the engineering understanding of vibration-assisted techniques for heavy oil extraction, highlighting the importance of frequency modulation combined with soaking periods, and paves the way for efficient design and application of the VS-GPC process in the field.